Liangxue Tongyu Prescription exerts neuroprotection by regulating the microbiota-gut-brain axis of rats with acute intracerebral hemorrhage - Yingying Sun; Dandan Zhou; Anlan Liu; Yu Zhou; Yang Zhao; Yuan Yuan; Weifeng Guo; Jianxiang Li (Brain Research Bulletin)
Liangxue Tongyu Prescription (LTP) is a classic herbal formula for treating acute intracerebral hemorrhage (AICH) in China. Previous studies have shown that LTP significantly ameliorates neurological impairments and gastrointestinal dysfunction in patients with AICH. However, the underlying molecular mechanism remains unclear. The aim of this study is to investigate whether LTP exerts its neuroprotective effect on AICH rats through the microbiota-gut-brain axis and explore its potential underlying mechanism. In the current study, AICH models were established by injecting autologous whole blood into the right caudate nucleus of rats. Behavioural and pathological evaluations demonstrated that LTP ameliorated neuronal and intestinal damage in AICH rats. Analysis via western blot, quantitative real-time PCR, immunohistochemistry (IHC) and tunel staining indicated that LTP upregulated the expression of brain-derived neurotrophic factor (BDNF) and nerve growth factor(NGF) and reduced neuronal cell apoptosis. Additionally, 16S rDNA sequencing revealed that LTP mitigated dysbiosis of intestinal microbiota in AICH rats. LTP increased the levels of noradrenaline (NA), dopamine (DA), glutamate (GLU) and modulated brain-gut peptides such as gastrin (GAS), motilin (MTL), ghrelin in AICH rats. Furthermore, LTP enhanced vagus nerve discharge. In summary, this research provides evidence suggesting that LTP’s influence on AICH may involve modulation of the microbiota-gut-brain axis, offering a potential scientific rationale for its therapeutic efficacy in improving outcomes of AICH.